On the Geolocation Bounds for Round-Trip Time-of-Arrival and All Non-Line-of-Sight Channels. (9th December 2007) - Mailaender Mailaender, Laurence Laurence
Abstract : The development of future geolocation systems requires a fundamental understanding of the importance of various system parameters, such as the number of sensors, the SNR, bandwidth, and channel conditions. We consider the bounds on time-based geolocation accuracy when all sensors experience non-line-of-sight (NLOS) conditions. While location accuracy generally improves with additional bandwidth, we find that NLOS effects place a limit on these gains. Our evaluation focuses on indoor geolocation where Rayleigh fading is present, different average SNR conditions occur on each link, and the sensors may not fully encircle the user. We introduce a new bound for round-trip time-of-arrival (RT-TOA) systems. We find that time-of-arrival (TOA) outperforms time-difference-of-arrival TDOA and RT-TOA, but the relative ordering of the latter two depends on the sensor geometry.